Post-traumatic endophthalmitis with retained intraocular foreign body – a case report with review of literature - Aggarwal, P; Garg, P; Sidhu, HK; Mehta, S (Nepalese Journal of Ophthalmology, 2012)
Introduction: Endophthalmitis following penetrating eye injuries has a poor prognosis and presents a diagnostic and therapeutic challenge. The aim of reporting this case was to identify the causative organism of post-traumatic endophthalmitis due to retained iron foreign body and to highlight the importance of carrying out diagnostic investigations. Case: A 20-year-old male presented with tenderness and blurring in the right eye 3 days after injury with an iron particle. Visual acuity was perception of light with accurate projection of rays in all quadrants. The slit-lamp examination revealed ciliary and conjuctival congestion. There was a verticallyoriented self-sealed, full-thickness laceration in the cornea adjacent to the limbus. The anterior chamber evaluation revealed + 4 cells, +3 flare and a 2 - mm hypopyon. There was cataract with a ruptured anterior lens capsule. Posterior synechae was present at 5’0 clock position. B-scan showed echogenic metallic foreign body in the posterior chamber, with vitreous opacities. The vitreous tap was done and intra-vitreal antibiotics injections of 1 mg in 0.1 ml vancomycin and 2.25 mg in 0.1 ml ceftazidime were given. Culture and sensitivity of the tap revealed staphylococcus as the causative agent. The patient was put on moxifloxacin eye drops, fortified tobramycin and cephazolin eye drops 1 hourly along with atropine eye drops. The patient was referred to the vitreoretinal surgeon urgently for pars plana vitrectomy and foreign body removal. At follow up, the patient’s BCVA was improved. Conclusion: The causative organism isolated was similar to that documented in other reports. Endophthalmitis must be treated with vitrectomy and intra-vitreal injections of antibiotics after a proper vitreous tap. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5875 NEPJOPH 2012; 4(1): 187-190